Development and characterization of breadnut (Artocarpus camansi) beverage. - Zosa, Karen May G. (2023.)
The demand for plant-based beverages has been a rising trend globally. It offers a better alternative to dairy beverages, ethically, environmentally, and health-wise, as consumers seek sustainable, healthy options. In this study, a plant-based beverage from breadnut (Artocarpus camansi) seeds was developed using a combination of different blanching and seed-to-water ratio processing treatments. Six different breadnut beverages were developed and subjected to sensory evaluation to determine its organoleptic characteristics and overall acceptability in terms of color, taste, and mouthfeel. It was found that beverage color is affected by the seed-to-water ratio and blanching techniques applied, since alkaline blanching darkens the color of the beverages while a higher seed-to-water ratio lightens it. However, beverage taste and mouthfeel were not significantly affected by the blanching techniques applied but were affected by the increasing seed-to-water ratio since noticeable differences exist between the treatments. As for the overall acceptability, the penalty analysis revealed that color, taste, and mouthfeel significantly impact the overall acceptability of breadnut beverages since it results in high mean drops per sensory attribute. Meanwhile, the most preferred formulation, based on the radar diagram, was the beverage with water-blanched seeds and a 1:1 seed-to-water ratio since it has high ratings for color, taste, and overall acceptability. It had a "too brown" color, a "just right" sweet taste, and a "just right" thick mouthfeel. Subsequently, it was characterized for its fat content, crude protein, and physicochemical properties, where it has 6.92% crude fat, 1.50% crude protein, 5.75 pH, 10.1°Bx, and 4.3 gcm viscosity. However, when subjected to consumer testing to determine public preference, it was found to be less preferred compared to the commercially available soy beverage. In order to have better sensory qualities than commercial plant-based beverages and similar sensory qualities to dairy beverages, the developed breadnut beverage needs further optimization.
Thesis (Undergraduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Breadnut beverage